Advances in endothelial shear stress proteomics - Firasat, Sabika; Hecker, Markus; Binder, Lutz; Asif, Abdul R. (Expert review of proteomics, 2014)
The vascular endothelium lining the luminal surface of all blood vessels is constantly exposed to shear stress exerted by the flowing blood. Blood flow with high laminar shear stress confers protection by activation of antiatherogenic, antithrombotic and anti-inflammatory proteins, whereas low or oscillatory shear stress may promote endothelial dysfunction, thereby contributing to cardiovascular disease. Despite the usefulness of proteomic techniques in medical research, however, there are relatively few reports on proteome analysis of cultured vascular endothelial cells employing conditions that mimic in vivo shear stress attributes. This review focuses on the proteome studies that have utilized cultured endothelial cells to identify molecular mediators of shear stress and the roles they play in the regulation of endothelial function, and their ensuing effect on vascular function in general. It provides an overview on current strategies in shear stress-related proteomics and the key proteins mediating its effects which have been characterized so far.
Gesehen am 22.07.2020